Agents of S.U.I.T - Green, John Patrick, 1975-; Hastings, Chris, 1983- (Green, John Patrick, 1975- InvestiGators (Series), 2023)
"At S.U.I.T. headquarters, Cilantro the Chameleon finally gets what she's been waiting for: a field assignment. Only...it's literally out in the middle of a field, and her orders are so vague, she can hardly tell what she's supposed to be investigating. But as she begins to uncover a sheep-led worker's rights revolt and an alien invasion conspiracy--not to mention a spooky haunting at the abandoned S.U.I.T. field outpost--Cilantro steps into her own V.E.S.T. as a valued member of the S.U.I.T. team"--